Prevalence and distribution of Cryptosporidium spp. in cattle in central and western Inner Mongolia, China - Ziran Mo; Bin Xu; Jingwei Quan; Qinghan Meng; Xu Jiang; Junyan Li; Jia Wang; Yaping Xuan; Xingyu Ruan; Wenbin Yang; Xiaoping Luo; Wei Hu (BMC Microbiology)
Abstract Cryptosporidium, an important zoonotic protozoan, poses a global threat to animal and human health, with cattle being recognized as susceptible hosts. Although Inner Mongolia is an important production and export base for beef, milk, and other cattle products, there is a paucity of comprehensive data on the prevalence of Cryptosporidium in cattle in the region. This study aims to investigate the prevalence and genetic characteristics of this parasite in the cattle populations of Inner Mongolia. From 2020 to 2021, 296 fecal samples were collected from cattle in five regions of Inner Mongolia. Nested PCR targeting the Cryptosporidium SSU rRNA gene, along with gp60 gene amplification for C. parvum subtype identification, was conducted. Phylogenetic and haplotype analyses were performed on positive sequences and the chi-square test was used to determine differences in infection rates between groups. The results showed an overall Cryptosporidium infection rate of 18.6% (55/296), which varied between regions, with Hohhot having the highest rate (27.5%, 30/109) and Ulanqab the lowest (5%, 3/60). Intensively farmed cattle had significantly higher infection rates (20.6%, 54/262) compared to non-intensive farms (2.9%, 1/34). Diarrheic calves had a higher prevalence (36.9%, 24/65) than non-diarrheic calves (20.3%, 13/64), while no significant in prevalence difference was observed in adult cattle. Calves exhibited a higher infection rate (25.3%, 37/146) than adult cattle (12.0%, 18/150). Five Cryptosporidium species were identified, with a predominance of C. bovis and C. parvum. Notably, all C. parvum belonged to the zoonotic IIdA15G1 subtype. Population genetic analysis indicated that C. bovis and C. parvum exhibited relatively homogeneous genetic structures, whereas C. ryanae showed significant genetic differentiation, likely driven by geographic isolation. This study sheds light on the epidemiology of cryptosporidiosis and highlights the potential risk of zoonotic transmission from cattle to humans in Inner Mongolia. The findings emphasize the urgent need for enhanced Cryptosporidium surveillance, prevention, and control measures in the region.